Implementasi Flutter Dalam Aplikasi Pencarian Rumah Kost Berbasis Mobile - Ambar Fisty; Dedi Bin Zainal; Wahyu Istalama Firdaus (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2023)
Palembang is one of the big cities that become targets for other cities people to find work or even continue their education. Most of the people from other cities are college students, as new college students who come from outside the city really need boarding houses as temporary residences in Palembang to make it easier for new college students to reach their place of education. Technological advances have played a major role in helping these new students to find boarding houses. One of them is this research that discusses boarding house rental applications that can make it easier for new college students to get boarding houses according to their wishes. This application can be run on the android system and there is a boarding profile ranging from facilities to a predetermined price. This application also uses Maps technology which has GPS in it so that users can easily see the location of the boarding house. Key words : Application, Boarding House, Android, Palembang, Google Maps